Knowledge, Motivation, and Accuracy of Anthropometric Measurement among Village Health Volunteers to Prevent Stunting in Aceh - Fadliady, Muchrizal; Asniar, Asniar; Aiyub, Aiyub (Jurnal KESANS : Kesehatan dan Sains, 2025)
Early detection and prevention of stunting are top priorities in improving child health outcomes in Indonesia. The village health volunteers play a strategic role in monitoring toddler growth through accurate anthropometric measurements. However, their levels of knowledge, motivation, and measurement precision vary considerably. This study aims to describe the knowledge, motivation, and accuracy of anthropometric measurements among village health volunteers in the early detection and prevention of stunting. A cross-sectional study design was employed, involving 110 village health volunteers in a rural district of Aceh, Indonesia. Data were collected through questionnaires and direct observations and analysed using univariate tests. The results indicate that the village health volunteers possess a medium level of knowledge, motivation, and accuracy in anthropometric measurement. The findings underscore the importance of enhancing the capacity of health volunteers through ongoing training, intensified supervision, and support from multiple stakeholders, thereby enabling village health volunteers to play a more effective role in the early detection and prevention of stunting